Arthroscopic Treatment of Femoral Neck Impingement Cysts Using Biocomposite Anchors in the Setting of Femoroacetabular Impingement - Hannah K. Day MS; Kent C. Doan MD; Trevor J. Shelton MD; Spencer M. Comfort BS; Marc J. Philippon MD (SAGE Publishing, 2022)
Background: There is no established superior treatment for femoral neck impingement cysts, which may be symptomatic and can create a challenge in the arthroscopic treatment of femoroacetabular impingement. Isolated decompression of these cysts may lead to biomechanical compromise and an increased risk of femoral neck fracture similar to that associated with cortical perforation in osteoplasty of cam lesions, given the remaining focal osseous disruption and cortical discontinuity analogous to a burr perforation. Indications: In patients undergoing arthroscopic treatment of femoroacetabular impingement and found to have femoral neck impingement cyst warranting decompression, occlusion of the remaining defect with a biocomposite anchor may improve symptoms related to the impingement cyst as well as reduce the risk of femoral neck fracture. Technique Description: This surgical technique video demonstrates the filling of a femoral neck impingement cyst using a case example of a very active middle-aged woman undergoing arthroscopic treatment of femoroacetabular impingement. During cam osteoplasty in the peripheral compartment phase, the cyst is decompressed using a curette. An appropriately sized bioabsorbable suture anchor is secured into the defect and the sutures removed. The osteoplasty is resumed over the screw to achieve contouring of the femoral neck commensurate with an adequate head-neck offset confirmed by dynamic intraoperative hip examination. Results: Postoperative imaging from this procedure reveals bony in-fill with gradual dissolution of the biocomposite anchor. In our cohort of patients treated with biocomposite anchors concomitant to arthroscopic treatment of femoracetabular impingement with follow-up ranging from 2 to 12 years, there were no self-reported femoral neck fractures. Discussion/Conclusion: We expect that treatment of femoral neck impingement cysts with biocomposite anchors will stimulate bony in-fill of the defect stimulated by the anchor, with a decrease in the risk of femoral neck fracture as compared with an untreated cyst. Further research is needed to strengthen the evidence surrounding comparative treatment of impingement cysts as well as the optimal choice of material in the case of occlusion with a biocomposite anchor.